Inorganic particle dispersed slurry composition and method for producing inorganic sintered body

By using the carboxya (methyl) acrylic resin that uses the boiling point of 200 ° C or above the boiling point of 200 ° C or more oxygen -oxygen, the oxidation problem of inorganic materials caused by high temperature discardment in the existing technology is solved. Realize the treatment of low -temperature dehydration adhesives and high fever, and improve the reliability of electronic components.

CN119384468APending Publication Date: 2025-01-28SEKISUI CHEMICAL CO LTD

Patent Information

Application Number
CN202380050676.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-07
Filing Date
2023-12-04
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, the degreasing process of acrylic binder needs to be carried out under a high temperature air atmosphere, resulting in the inorganic material being easily oxidized, and the solvent selectivity of propylene glycol carbonate is insufficient, affecting the storage stability of the inorganic particle dispersion slurry.

Method used

The carboxylic anhydrin anhydrin anhydrial anhydrodicida with a boiling point of 200 ° C and the oxygen atomic content is more than 40%or more as a dehydrator, combined with a specific structure (methyl) acrylic resin, the forming of inorganic particle decentralized slurry compositions can be formed. Perrace the bonding agent at low temperature to inhibit the oxidation of inorganic particles and improve sintering after firing.

Benefits of technology

The high storage stability and excellent printing properties of inorganic particle decentralized slurry compositions can be achieved. It can effectively remove adhesive treatment at low temperature, reduce the residual carbon after firing, and improve the reliability of electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

Provided is an inorganic particle-dispersed slurry composition which has excellent storage stability and printability, is capable of promoting a debinding treatment even at low temperatures, is capable of suppressing oxidation of inorganic particles, has little residual carbon after firing, has excellent sinterability, and is capable of obtaining a highly reliable electronic component. Also provided is a method for producing an inorganic sintered body using the slurry composition. The present invention is an inorganic particle dispersed slurry composition containing a binder resin (A), inorganic particles (B), and a solvent (C), and further containing a carboxylic acid anhydride having a boiling point of 200 DEG C or more and an oxygen atom content of 40 wt% or more as a debinder aid (D).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing an inorganic particle-dispersed slurry composition and an inorganic sintered body. Background Art

[0002] Inorganic particle dispersion slurry compositions in which inorganic particles such as ceramic powder and glass particles are dispersed in a binder resin are used in the production of various electronic components. These slurry compositions are formed into sheets through coating and drying steps, which are called green sheets.

[0003] Ceramic green sheets containing inorganic particles and a binder resin are stacked with electrode layers formed thereon by screen printing or the like, and the stacked body is heated in a firing furnace to decompose and remove the binder resin contained therein and sinter the inorganic particles, thereby manufacturing various electronic components.

[0004] Due to the increasing need for sustainable business processes in recent years, there is a demand for binder resins that can be debonded at lower temperatures and in shorter times. Low-temperature treatment not only reduces the energy required for heating furnaces, but also prevents thermal and oxidative degradation of inorganic components in electronic components, allowing the production of electronic components with higher reliability.

[0005] In Patent Document 1, a low-temperature decomposable acrylic binder is used in the manufacture of an all-solid-state battery, and degreasing is performed by heating from room temperature to 500° C. at a heating rate of 20° C. / min in air and maintaining at 500° C. for 30 minutes.

[0006] In addition, in Patent Document 2, aliphatic polypropylene carbonate is used as a low-temperature decomposition binder in a low-melting-point glass paste to manufacture a sealing material for electronic components. At this time, the temperature is raised to 430° C. in a nitrogen atmosphere, and the firing temperature is maintained for 10 minutes, and then cooled to room temperature to perform degreasing, and the glass paste is fired.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2018-77989

[0010] Patent Document 2: Japanese Patent Application Publication No. 2011-178606 Summary of the invention

[0011] Problems to be solved by the invention

[0012] Acrylic binders have high solvent selectivity and are easy to adjust resin strength. Therefore, according to the method described in Patent Document 1, a slurry composition for making green sheets can be provided. However, degreasing requires a high temperature of 500° C. in an air atmosphere, and there is a problem that performance degradation such as oxidation is easily caused depending on the inorganic material used.

[0013] In addition, although propylene carbonate described in Patent Document 2 is more decomposable than acrylic resin in a nitrogen atmosphere, it lacks solvent selectivity and decomposes in an environment other than a neutral pH, which causes problems in the storage stability of the inorganic particle dispersion slurry.

[0014] The object of the present invention is to provide an inorganic particle dispersion slurry composition, which has excellent storage stability and printability, can promote the debindering process even at low temperatures, can inhibit the oxidation of inorganic particles, has little residual carbon after firing and excellent sintering properties, and can obtain highly reliable electronic components. In addition, the object of the present invention is to provide a method for producing an inorganic sintered body using the slurry composition.

[0015] Means for solving problems

[0016] The present invention (1) relates to an inorganic particle dispersion slurry composition, which contains a binder resin (A), inorganic particles (B) and a solvent (C), and the inorganic particle dispersion slurry composition further contains a carboxylic anhydride having a boiling point of 200° C. or higher and an oxygen atom content of 40 wt % or higher as a binder removal aid (D).

[0017] The present invention (2) relates to the inorganic particle dispersion slurry composition of the present invention (1), wherein the carboxylic acid anhydride is an anhydride of at least one carboxylic acid selected from succinic acid, maleic acid, citric acid, glutaric acid, diglycolic acid, methoxyacetic acid, itaconic acid, citraconic acid, trimellitic acid, cyclobutanetetracarboxylic acid, propanetricarboxylic acid, butanetetracarboxylic acid, and cyclopentanetetracarboxylic acid.

[0018] The present invention (3) relates to the inorganic particle-dispersed slurry composition of the present invention (1) or (2), wherein the content of the carboxylic anhydride is 5 parts by weight or more and 30 parts by weight or less based on 100 parts by weight of the binder resin (A).

[0019] The present invention (4) relates to an inorganic particle-dispersed slurry composition according to any combination of any of the present inventions (1) to (3), wherein the binder resin (A) comprises a (meth)acrylic resin.

[0020] The present invention (5) relates to the inorganic particle-dispersed slurry composition of the present invention (4), wherein the (meth)acrylic resin contains 50% by weight or more of a segment derived from a (meth)acrylic acid ester having 4 or more carbon atoms in an ester substituent and having a branched structure in the ester substituent.

[0021] The present invention (6) relates to a method for producing an inorganic sintered body, comprising: a step of drying the inorganic particle dispersion slurry composition according to any one of the present inventions (1) to (5) to obtain an inorganic particle dispersion compact; and a step of degreasing the inorganic particle dispersion compact at a temperature below 300°C.

[0022] Hereinafter, the present invention will be described in detail.

[0023] The present inventors have conducted intensive research and found that a slurry composition containing a binder resin and a debindering aid having a specific structure has excellent storage stability and printability. In addition, it was found that when the slurry composition is used in the manufacture of an inorganic sintered body, the debindering process can be promoted even at low temperatures, the oxidation of inorganic particles can be suppressed, the residual carbon after sintering is small and the sintering property is excellent, and electronic components with high reliability can be produced, thereby completing the present invention.

[0024] <Binder resin (A)>

[0025] The slurry composition contains a binder resin (A).

[0026] Examples of the binder resin (A) include (meth)acrylic resins, polystyrene resins, polyvinyl acetate resins, polyacetal resins, polycarbonate resins, etc. Among them, (meth)acrylic resins are preferred because of their excellent low-temperature decomposability.

[0027] In the slurry composition, by combining a (meth)acrylic resin with a carboxylic anhydride described below, the binder removal treatment can be performed at a low temperature in a nitrogen atmosphere without using oxygen, and oxidation of the inorganic particles can be suppressed.

[0028] In addition, by combining a (meth)acrylic resin with the above-mentioned other binder resin as the binder resin (A), it is possible to further improve the low-temperature decomposability.

[0029] The weight average molecular weight (Mw) of the binder resin (A) is preferably 20,000 or more and preferably 4,000,000 or less.

[0030] If the Mw is 20,000 or more, the viscosity of the slurry composition will not be too low, and the dispersibility of the inorganic particles can be improved. If the Mw is 4,000,000 or less, the coating strength can be improved, and the viscosity of the slurry composition is sufficiently increased, so that the storage stability is improved and the printability can be excellent.

[0031] The Mw is preferably 30,000 or more, more preferably 40,000 or more, preferably 3,000,000 or less, more preferably 2,000,000 or less, further preferably 1,000,000 or less, and further preferably 500,000 or less. The Mw is preferably 20,000 to 4,000,000, more preferably 30,000 to 3,000,000, further preferably 40,000 to 2,000,000, further preferably 40,000 to 1,000,000, and particularly preferably 40,000 to 500,000.

[0032] The glass transition temperature (Tg) of the binder resin (A) is preferably 20°C or higher, more preferably 30°C or higher, and even more preferably 40°C or higher, and is preferably 80°C or lower, more preferably 70°C or lower, even more preferably 60°C or lower, and even more preferably 50°C or lower. The Tg is preferably 20 to 80°C, more preferably 30 to 70°C, even more preferably 40 to 60°C, and even more preferably 40 to 50°C.

[0033] In addition, the said glass transition temperature (Tg) can be measured using a differential scanning calorimeter (DSC) etc., for example.

[0034] The content of the binder resin (A) in the slurry composition is not particularly limited, but is preferably 3% by weight or more, more preferably 4% by weight or more, further preferably 5% by weight or more, further preferably 6% by weight or more, and preferably 30% by weight or less, more preferably 20% by weight or less, further preferably 12% by weight or less. The content of the binder resin (A) is preferably 3 to 30% by weight, more preferably 4 to 20% by weight, further preferably 5 to 12% by weight, further preferably 6 to 12% by weight.

[0035] By setting the content of the binder resin to be within the above range, a slurry composition that can be fired at a low temperature can be produced.

[0036] The binder resin (A) preferably contains a (meth)acrylic resin.

[0037] The (meth)acrylic resin preferably has a segment derived from a (meth)acrylic acid ester having a branched structure in an ester substituent.

[0038] The decomposition end temperature of a (meth)acrylic resin mainly composed of a (meth)acrylic acid ester having a branched structure in an ester substituent is lower than the decomposition end temperature of a (meth)acrylic acid ester mainly composed of a (meth)acrylic acid ester having a linear ester substituent. (Meth)acrylic acid resins show a depolymerization reaction in which they decompose into monomers under an environment exceeding the upper limit temperature (Japanese: ceiling temperature), but (meth)acrylic acid esters having a branched structure in an ester substituent have the characteristic of being difficult to polymerize again, and therefore have a low decomposition end temperature. Therefore, the (meth)acrylic acid resin having the above structure is excellent in low-temperature decomposition.

[0039] Examples of the (meth)acrylate having a branched structure in the ester substituent include (meth)acrylate alkyl esters having a branched alkyl group and (meth)acrylate polyalkylene glycol esters having an alkylene glycol unit having a branched structure.

[0040] The number of carbon atoms in the ester substituent is preferably 3 or more, more preferably 4 or more, preferably 20 or less, more preferably 15 or less, further preferably 12 or less, for example 10 or less. The number of carbon atoms in the ester substituent is preferably 3-20, more preferably 4-15, further preferably 4-12, further preferably 4-10.

[0041] Examples of the alkyl (meth)acrylate having a branched alkyl group include isopropyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isopentyl (meth)acrylate, isohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, and isodecyl (meth)acrylate.

[0042] Among them, isopropyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and isodecyl (meth)acrylate are preferred; isopropyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, 2-ethylhexyl methacrylate, and isodecyl methacrylate are more preferred; and isobutyl methacrylate and 2-ethylhexyl methacrylate are further preferred.

[0043] Examples of the polyalkylene glycol (meth)acrylate having an alkylene glycol unit having a branched structure include polyalkylene glycol (meth)acrylate having a propylene glycol unit. In addition, the polyalkylene glycol (meth)acrylate having an alkylene glycol unit having a branched structure may have an alkoxy group at the terminal. Examples of the alkoxy group include a methoxy group, an ethoxy group, and a butoxy group.

[0044] The number of alkylene glycol units in the (meth)acrylic acid polyalkylene glycol ester having an alkylene glycol unit having a branched structure is preferably 3 or more, more preferably 4 or more, and is preferably 10 or less, more preferably 8 or less. The number of alkylene glycol units is preferably 3-10, more preferably 4-8.

[0045] The content of the segment derived from the (meth)acrylic acid ester having a branched structure in the ester substituent in the (meth)acrylic resin is preferably 50% by weight or more.

[0046] When it is within the above range, it is possible to obtain a slurry composition having more excellent low-temperature decomposability.

[0047] The content of the segment derived from the (meth)acrylate having a branched structure in the ester substituent is more preferably 60% by weight or more, further preferably 70% by weight or more, preferably 100% by weight or less, and more preferably 90% by weight or less. The content of the segment derived from the (meth)acrylate having a branched structure in the ester substituent is preferably 50 to 100% by weight, more preferably 60 to 100% by weight, and further preferably 70 to 90% by weight.

[0048] The above content can be measured by, for example, thermal decomposition GC-MS.

[0049] The (meth)acrylic resin preferably has a segment derived from a (meth)acrylic acid ester having 4 or more carbon atoms in the ester substituent and having a branched structure in the ester substituent.

[0050] By having the above-mentioned configuration, it is possible to obtain a slurry composition having more excellent low-temperature decomposability.

[0051] The (meth)acrylic resin preferably has at least one selected from the group consisting of a segment derived from isobutyl methacrylate, a segment derived from 2-ethylhexyl methacrylate, a segment derived from isodecyl methacrylate, and a segment derived from isononyl methacrylate as a segment derived from a (meth)acrylic acid ester having a branched structure in an ester substituent.

[0052] By having the above-mentioned configuration, it is possible to obtain a slurry composition having more excellent low-temperature decomposability.

[0053] The (meth)acrylic resin preferably contains a segment derived from a (meth)acrylate ester having 4 or more carbon atoms in the ester substituent and having a branched structure in the ester substituent in an amount of 50% by weight or more.

[0054] When it is within the above range, it is possible to obtain a slurry composition having more excellent low-temperature decomposability.

[0055] The content of the segment derived from the (meth)acrylate having 4 or more carbon atoms in the ester substituent and having a branched structure in the ester substituent is more preferably 60% by weight or more, and further preferably 70% by weight or more, for example, 100% by weight or less, preferably 90% by weight or less, and further preferably 80% by weight or less. The content of the segment derived from the (meth)acrylate having 4 or more carbon atoms in the ester substituent and having a branched structure in the ester substituent is preferably 50 to 100% by weight, more preferably 60 to 90% by weight, and further preferably 70 to 80% by weight.

[0056] The (meth)acrylic resin may further include other segments such as a segment derived from (meth)acrylate in which the ester substituent is linear and a segment derived from (meth)acrylate in which the ester substituent has a cyclic structure.

[0057] By having the above-mentioned structure, the coating film strength can be improved.

[0058] Examples of the (meth)acrylate in which the ester substituent is linear include (meth)acrylate alkyl esters having a linear alkyl group and (meth)acrylate polyalkylene glycol esters having a linear alkylene glycol unit.

[0059] The number of carbon atoms in the ester substituent is preferably 1 or more, more preferably 2 or more, and preferably 10 or less, more preferably 6 or less. The number of carbon atoms in the ester substituent is preferably 1-10, more preferably 2-6.

[0060] Examples of the (meth)acrylic acid alkyl ester having a linear alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, and n-hexyl (meth)acrylate. Among them, methyl (meth)acrylate, ethyl (meth)acrylate, and n-butyl (meth)acrylate are preferred, and methyl methacrylate, ethyl methacrylate, and n-butyl methacrylate are more preferred. In addition, from the perspective of being able to prepare a slurry composition with better low-temperature decomposability, the (meth)acrylic resin further preferably has a segment derived from n-butyl methacrylate.

[0061] As the above-mentioned (meth) acrylic acid polyalkylene glycol ester having a linear alkylene glycol unit, there can be mentioned: (meth) acrylic acid polyalkylene glycol ester having an ethylene glycol unit, (meth) acrylic acid polyalkylene glycol ester having a 1,3-propylene glycol unit, etc. In addition, the above-mentioned (meth) acrylic acid polyalkylene glycol ester having a linear alkylene glycol unit may have an alkoxy group at the end. As the above-mentioned alkoxy group, for example, a methoxy group, an ethoxy group, a butoxy group, etc. can be mentioned. The above-mentioned alkoxy group does not have a branched structure. Among them, preferably, it is a (meth) acrylic acid polyalkylene glycol ester having an ethylene glycol unit, and more preferably, it is a (meth) acrylic acid methoxy polyethylene glycol ester.

[0062] The number of alkylene glycol units in the polyalkylene glycol (meth)acrylate having a linear alkylene glycol unit is preferably 4 or more, more preferably 10 or more, and is preferably 23 or less, more preferably 20 or less. The number of alkylene glycol units is preferably 4-23, more preferably 10-20.

[0063] Examples of the (meth)acrylate having a cyclic structure in the ester substituent include (meth)acrylates having a cyclic alkyl group such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate, and (meth)acrylates having a glycidyl group such as glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, and 3,4-epoxycyclohexyl methyl (meth)acrylate.

[0064] In particular, the (meth)acrylic resin preferably uses a substance containing a large amount of oxygen as a monomer. (meth)acrylic acid polyalkylene glycol ester having a linear polyalkylene glycol unit has a large oxygen content and preferably has a segment derived from such a (meth)acrylic acid ester.

[0065] The depolymerization reaction of the (meth)acrylic resin is an endothermic reaction, and it is difficult to obtain the heat required for decomposition in low-temperature decomposition. By having a segment derived from a monomer containing a large amount of oxygen as described above, the (meth)acrylic resin can be combusted and decomposed using its own oxygen at around the upper limit temperature of the (meth)acrylic resin even in a nitrogen atmosphere, thereby further improving the low-temperature decomposition property.

[0066] The oxygen composition ratio of the polyalkylene glycol (meth)acrylate having a linear alkylene glycol unit is preferably 30% by weight or more, and more preferably 35% by weight or more.

[0067] The content of the segment derived from the (meth)acrylate whose ester substituent is a linear chain in the (meth)acrylic resin is, for example, 0% by weight or more, preferably 1% by weight or more, more preferably 5% by weight or more, further preferably 10% by weight or more, preferably 40% by weight or less, more preferably 30% by weight or less. The content of the segment derived from the (meth)acrylate whose ester substituent is a linear chain is preferably 0 to 40% by weight, more preferably 1 to 30% by weight, further preferably 5 to 30% by weight, and further preferably 10 to 30% by weight.

[0068] By setting it as the said range, handling properties, such as printing property, are improved.

[0069] The above content can be measured by, for example, thermal decomposition GC-MS.

[0070] The total content of the segment derived from isobutyl methacrylate, the segment derived from n-butyl methacrylate, and the segment derived from 2-ethylhexyl methacrylate in the (meth)acrylic resin is preferably 70% by weight or more.

[0071] By satisfying the above-mentioned constitution, it is possible to obtain a slurry composition having more excellent low-temperature decomposability.

[0072] The above-mentioned total content is more preferably 75% by weight or more, and more preferably 80% by weight or more. The upper limit is not particularly limited, for example, 100% by weight or less, and more preferably 90% by weight or less. The above-mentioned total content is preferably 70 to 100% by weight, more preferably 75 to 90% by weight, and more preferably 80 to 90% by weight.

[0073] The above content can be measured by, for example, thermal decomposition GC-MS.

[0074] The (meth)acrylic resin may have a segment derived from a (meth)acrylate having a glycidyl group, a carboxyl group, or a hydroxyl group.

[0075] Examples of the (meth)acrylate having a glycidyl group include glycidyl (meth)acrylate, 4-hydroxybutyl acrylate glycidyl ether, and 3,4-epoxycyclohexylmethyl methacrylate.

[0076] Examples of the (meth)acrylate having a hydroxyl group or a carboxyl group include 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and (meth)acrylic acid.

[0077] The content of the segment derived from the (meth)acrylate having a glycidyl group, a carboxyl group or a hydroxyl group in the (meth)acrylic resin is preferably 1% by weight or more, more preferably 4% by weight or more, and preferably 10% by weight or less, more preferably 7% by weight or less. The content of the segment derived from the (meth)acrylate having a glycidyl group, a carboxyl group or a hydroxyl group is preferably 1 to 10% by weight, more preferably 4 to 7% by weight.

[0078] By setting it as the said range, low-temperature decomposability can be further improved, and the toughness of the obtained inorganic particle-dispersed sheet can be improved.

[0079] The weight average molecular weight (Mw) of the (meth)acrylic resin is preferably 20,000 or more and preferably 4,000,000 or less.

[0080] If the Mw is 20,000 or more, the viscosity of the slurry composition will not be too low, and the dispersibility of the inorganic particles can be improved. If the Mw is 4,000,000 or less, the coating strength can be improved, and the viscosity of the slurry composition is sufficiently increased, so that the storage stability is improved and the printability can be excellent.

[0081] The Mw is preferably 30,000 or more, more preferably 40,000 or more, preferably 3,000,000 or less, more preferably 2,000,000 or less, further preferably 1,000,000 or less, and further preferably 500,000 or less. The Mw is preferably 20,000 to 4,000,000, more preferably 30,000 to 3,000,000, further preferably 40,000 to 2,000,000, further preferably 40,000 to 1,000,000, and particularly preferably 40,000 to 500,000.

[0082] The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the (meth)acrylic resin is usually 1 or more, preferably 1.5 or more, more preferably 2 or more, and preferably 5 or less, more preferably 3 or less. The Mw / Mn is preferably 1 to 5, more preferably 1.5 to 3, and even more preferably 2 to 3.

[0083] By setting it as the said range, since the component of a low degree of polymerization is contained appropriately, the viscosity of a slurry composition will be in the suitable range, and productivity can be improved.

[0084] The weight average molecular weight (Mw) and the number average molecular weight (Mn) are average molecular weights based on polystyrene conversion and can be obtained by, for example, GPC measurement using a column LF-804 (manufactured by Showa Denko K.K.) as a column.

[0085] The glass transition temperature (Tg) of the (meth)acrylic resin is preferably 20°C or higher, more preferably 30°C or higher, and even more preferably 40°C or higher, and is preferably 80°C or lower, more preferably 70°C or lower, even more preferably 60°C or lower, and even more preferably 50°C or lower. The Tg is preferably 20 to 80°C, more preferably 30 to 70°C, even more preferably 40 to 60°C, and even more preferably 40 to 50°C.

[0086] In addition, the said glass transition temperature (Tg) can be measured using a differential scanning calorimeter (DSC) etc., for example.

[0087] The content of the (meth)acrylic resin in the binder resin (A) is preferably 10% by weight or more and 100% by weight or less, more preferably 40% by weight or more and more preferably 50% by weight or less.

[0088] The content of the (meth) acrylic resin in the slurry composition is not particularly limited, but is preferably 3% by weight or more, more preferably 4% by weight or more, further preferably 5% by weight or more, further preferably 6% by weight or more, and preferably 30% by weight or less, more preferably 20% by weight or less, further preferably 12% by weight or less. The content of the (meth) acrylic resin is preferably 3 to 30% by weight, more preferably 4 to 20% by weight, further preferably 5 to 12% by weight, further preferably 6 to 12% by weight.

[0089] By setting the content of the (meth)acrylic resin to be within the above range, a slurry composition that can be fired at a low temperature can be produced.

[0090] The method for producing the (meth)acrylic resin is not particularly limited. For example, the following method may be mentioned: first, an organic solvent or the like is added to a raw material monomer mixture containing a (meth)acrylic ester having a branched structure in an ester substituent, etc. to prepare a monomer mixed solution, and further, a polymerization initiator is added to the obtained monomer mixed solution to polymerize the obtained monomer mixed solution to produce the (meth)acrylic resin.

[0091] The method for polymerization is not particularly limited, and examples thereof include emulsion polymerization, suspension polymerization, bulk polymerization, interfacial polymerization, solution polymerization, etc. Among them, solution polymerization is preferred.

[0092] Examples of the polymerization initiator include dilauroyl peroxide, p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroxyperoxide, tert-butyl hydroxyperoxide, cyclohexanone peroxide, disuccinic acid peroxide, potassium persulfate, and ammonium persulfate.

[0093] Examples of commercial products thereof include PERMENTA H, PERCUMYL P, PEROCTA H, PERCUMYL H-80, PEROYL 355, PERBUTYL H-69, PERHEXA H, PEROYL SA, and PEROYL L (all manufactured by NOF Corporation), TRIGONOX 27, and TRIGONOX 421 (all manufactured by Nouryon).

[0094] <Inorganic particles (B)>

[0095] The slurry composition contains inorganic particles.

[0096] Examples of the inorganic particles include ceramic powder, glass powder, phosphor particles, silicon oxide, and metal particles.

[0097] Examples of the ceramic powder include aluminum oxide, ferrite, zirconium oxide, zircon, barium zirconate, calcium zirconate, titanium oxide, barium titanate, strontium titanate, calcium titanate, magnesium titanate, zinc titanate, lanthanum titanate, neodymium titanate, lead zirconate titanate, aluminum oxide nitride, silicon nitride, boron nitride, gallium nitride, boron carbide, barium stannate, calcium stannate, magnesium silicate, mullite, steatite, cordierite, forsterite, and the like.

[0098] In addition, ITO, FTO, niobium oxide, vanadium oxide, tungsten oxide, strontium lanthanum manganate, lanthanum strontium cobalt ferrite, yttrium-stabilized zirconia, gadolinium-doped cerium oxide, nickel oxide, lanthanum chromate, Sm 2 Fe 17 N 3 、Nd 2 Fe 14 B, MnAlC, L 10 FeNi、La 2 / 3- x Li 3x TiO 3 ,La (1-x) / 3 Li x NbO 3 、LaGaO 3 、LaScO 3 、CaZrO 3, (La 0.875 Sr 0.125 )MnO 3 、PbZrTiO 3 、SrBi 2 Ta 2 O 9 、BiFeO 3 , KNbO 3 、PbVO 3 、BiCo 3 、Bi(Zn 1 / 2 Ti 1 / 2 ) 3 wait.

[0099] By using the above-mentioned ceramic powder, the composition can be suitably used as a slurry composition for ceramic green sheets.

[0100] Examples of the glass powder include glass powders such as bismuth oxide glass, silicate glass, lead glass, zinc glass, and boron glass; and CaO—Al 2 O 3 -SiO 2 System, MgO-Al 2 O 3 -SiO 2 Series, LiO 2 -Al 2 O 3 -SiO 2 Glass powders of various silicon oxides, etc.

[0101] In addition, SnO-B can also be used as the above-mentioned glass powder. 2 O 3 -P 2 O 5 -Al 2 O 3 Mixture, PbO-B 2 O 3 -SiO 2 Mixture, BaO-ZnO-B 2 O 3 -SiO 2 Mixture, ZnO-Bi 2 O 3 -B 2 O 3 -SiO 2 Mixture, Bi 2 O 3 -B 2 O 3 -BaO-CuO mixture, Bi 2 O 3 -ZnO-B 2 O3 -Al 2 O 3 -SrO mixture, ZnO-Bi 2 O 3 -B 2 O 3 Mixture, Bi 2 O 3 -SiO 2 Mixture, P 2 O 5 -Na 2 O-CaO-BaO-Al 2 O 3 -B 2 O 3 Mixture, P 2 O 5 -SnO mixture, P 2 O 5 -SnO-B 2 O 3 Mixture, P 2 O 5 -SnO-SiO 2 Mixture, CuO-P 2 O 5 -RO mixture, SiO 2 -B 2 O 3 -ZnO-Na 2 O-Li 2 O-NaF-V 2 O 5 Mixture, P 2 O 5 -ZnO-SnO-R 2 O-RO mixture, B 2 O 3 -SiO 2 -ZnO mixture, B 2 O 3 -SiO 2 -Al 2 O 3 -ZrO 2 Mixture, SiO 2 -B 2 O 3 -ZnO-R 2 O-RO mixture, SiO 2 -B 2 O 3 -Al 2 O 3 -RO-R 2 O mixture, SrO-ZnO-P 2 O5 Mixture, SrO-ZnO-P 2 O 5 Mixture, BaO-ZnO-B 2 O 3 -SiO 2 mixture, etc. In addition, R represents an element selected from Zn, Ba, Ca, Mg, Sr, Sn, Ni, Fe and Mn.

[0102] PbO-B is particularly preferred 2 O 3 -SiO 2 Mixed glass powder, lead-free BaO-ZnO-B 2 O 3 -SiO 2 Mixture or ZnO-Bi 2 O 3 -B 2 O 3 -SiO 2 Mixtures such as lead-free glass powder.

[0103] The inorganic particles contain lithium, and thus can be suitably used as an electrolyte slurry composition for an all-solid-state lithium-ion battery. Specific examples of the inorganic particles containing lithium include: LiO 2 -Al 2 O 3 -SiO 2 Low melting point glass such as inorganic glass, Li 2 Lithium sulfide glass such as S-MxSy (M=B, Si, Ge, P), LiCoO 2 Lithium cobalt composite oxide, LiMnO 4 Lithium manganese composite oxides, lithium nickel composite oxides, lithium vanadium composite oxides, lithium zirconium composite oxides, lithium hafnium composite oxides, lithium phosphosilicate (Li 3.5 Si 0.5 P 0.5 O 4 )、LiTiO2 2 (PO 4 ) 3 )、Lithium titanate(Li 4 Ti 5 O 12 )、Li 4 / 3 Ti 5 / 3 O 4 、LiGe 2 (PO 4 ) 3 )、Li 2 -SiS glass, Li 4 G JZ4 -Li 3 PS 4 Glass, LiSiO 3 、LiMn 2 O 4 , Li 2 SP 2 S 5 Glass, ceramics, Li 2 O-SiO 2 , Li 2 OV 2 O 5 -SiO 2 、LiS-SiS 2 -Li 4 SiO 4 Glass, LiPON plasma conductive oxide, Li 2 OP 2 O 5 -B 2 O 3 , Li 2 O-GeO 2 Ba and other lithium oxide compounds, LixAlyTiz (PO 4 ) 3 Glass, LaxLiyTiOz Glass, LixGeyPzO 4 Glass, Li 7 La 3 Zr 2 O 12 Glass, LivSiwPxSyClz Glass, LiNbO 3 Lithium niobium oxides, Li-β-alumina and other lithium alumina compounds, Li 14 Zn(GeO 4 ) 4 Lithium zinc oxide, etc.

[0104] The phosphor particles are not particularly limited. For example, as the phosphor material, a blue phosphor material, a red phosphor material, a green phosphor material, etc., which are known as phosphor materials for displays, can be used. As the blue phosphor material, for example, MgAl 10 O 17 :Eu, Y 2 SiO 5 :Ce series, CaWO 4 : Pb series, BaMgAl 14 O 23 :Eu series, BaMgAl 16 O 27 :Eu series, BaMg 2 Al14 O 23 :Eu series, BaMg 2 Al 14 O 27 : Eu-based, ZnS: (Ag, Cd)-based. As the red phosphor material, for example, Y 2 O 3 :Eu series, Y 2 SiO 5 :Eu series, Y 3 Al 5 O 12 :Eu series, Zn 3 (PO 4 ) 2 : Mn series, YBO 3 :Eu series, (Y, Gd) BO 3 :Eu series, GdBO 3 :Eu series, ScBO 3 :Eu series, LuBO 3 : Eu-based substances. As green phosphor substances, for example, Zn 2 SiO 4 :Mn series, BaAl 12 O 19 :Mn series, SrAl 13 O 19 : Mn series, CaAl 12 O 19 : Mn series, YBO 3 :Tb series, BaMgAl 14 O 23 :Mn series, LuBO 3 :Tb series, GdBO 3 :Tb series, ScBO 3 :Tb series, Sr 6 Si 3 O 3 Cl 4 : Eu-based substances. In addition, ZnO: Zn-based, ZnS: (Cu, Al)-based, ZnS: Ag-based, Y 2 O 2 S: Eu series, ZnS: Zn series, (Y, Cd) BO 3 :Eu series, BaMgAl 12 O 23 : Eu series substances.

[0105] The metal particles are not particularly limited, and examples thereof include powders containing iron, copper, nickel, palladium, platinum, gold, silver, aluminum, tungsten, and alloys thereof.

[0106] In addition, metals such as copper and iron that have good adsorption characteristics with carboxyl groups, amino groups, amide groups, etc. and are easily oxidized can also be used appropriately. These metal powders can be used alone or in combination of two or more.

[0107] In addition to the metal complex, various carbon blacks, carbon nanotubes, and the like can also be used.

[0108] The average particle size of the inorganic particles is preferably 0.1 μm or more, more preferably 0.5 μm or more, and preferably 100 μm or less, more preferably 50 μm or less. The average particle size is preferably 0.1 to 100 μm, more preferably 0.5 to 50 μm.

[0109] When the content is within the above range, the specific surface area of ​​the inorganic particles will not become too large, and a dense molded body can be obtained by firing.

[0110] The average particle size of the inorganic particles can be measured, for example, by observation using a transmission electron microscope or by a light scattering method using a dispersion liquid.

[0111] The content of the inorganic particles in the slurry composition is not particularly limited, but is preferably 40% by weight or more, and preferably 90% by weight or less. By setting the above range, the density of the inorganic particles can be fully increased. In addition, the dispersibility of the inorganic particles can be fully increased, and the formability can be improved. The content of the inorganic particles is preferably 40 to 90% by weight.

[0112] <Solvent (C)>

[0113] The above-mentioned slurry composition contains a solvent.

[0114] The above-mentioned solvent is not particularly limited. When producing an inorganic particle-dispersed sheet, a solvent having excellent coating properties, drying properties, dispersibility of inorganic particles, etc. is preferably used.

[0115] Examples of the solvent include alcohols such as aliphatic alcohols, glycols, terpene alcohols, and aromatic alcohols, aromatic hydrocarbons, esters, ketones, and N-methylpyrrolidone.

[0116] Examples of the aliphatic alcohols include ethanol and isopropanol.

[0117] Examples of the diols include ethylene glycol monobutyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoisobutyl ether, butyl carbitol, ethylene glycol monoethyl ether acetate, trimethylpentanediol monoisobutyrate, butyl carbitol acetate, Texanol, ethylene glycol monophenyl ether, propylene glycol monophenyl ether, ethylene glycol ethyl ether, and ethyl carbitol acetate.

[0118] Examples of the terpene alcohols include terpineol, dihydroterpineol, terpineol acetate, and dihydroterpineol acetate.

[0119] Examples of the aromatic alcohols include benzyl alcohol, ethylene glycol monophenyl ether, propylene glycol monophenyl ether, and cresol.

[0120] Examples of the aromatic hydrocarbons include toluene and the like.

[0121] Examples of the esters include ethyl acetate, butyl acetate, hexyl acetate, isoamyl acetate, butyl butyrate, methoxybutyl acetate, butyl lactate, dioctyl phthalate, and dioctyl adipate.

[0122] Examples of the ketones include methyl ethyl ketone, methyl isobutyl ketone, and isophorone.

[0123] Among them, butyl acetate, hexyl acetate, butyl butyrate, isoamyl acetate, methoxybutyl acetate, ethyl carbitol acetate, terpineol, terpineol acetate, dihydroterpineol, dihydroterpineol acetate, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoisobutyl ether, butyl carbitol, butyl carbitol acetate, and Texanol are preferred; butyl acetate, hexyl acetate, terpineol, and ethyl carbitol acetate are more preferred; and butyl acetate, terpineol, and benzyl alcohol are further preferred.

[0124] It should be noted that these organic solvents may be used alone or in combination of two or more. In one embodiment of the present invention, the organic solvent is different from the above-mentioned binder removal auxiliary agent.

[0125] The boiling point of the solvent is preferably 90°C or higher, preferably 230°C or lower, more preferably 120°C or higher, more preferably 210°C or lower. The boiling point is preferably 90 to 230°C, more preferably 120 to 210°C.

[0126] When the content is within the above range, evaporation does not occur too quickly, and drying can be easily performed using a blower oven, etc. In addition, printability can be improved, and a coated article having a smooth surface can be obtained.

[0127] The content of the solvent in the slurry composition is preferably 10% by weight or more, and preferably 60% by weight or less, more preferably 20% by weight or more, and more preferably 50% by weight or less.

[0128] By setting it as the said range, coating property and the dispersibility of inorganic particles can be further improved. The content of the said solvent is preferably 10-60 weight%, and more preferably 20-50 weight%.

[0129] <Binder removal aid (D)>

[0130] The slurry composition contains a binder removal aid.

[0131] The binder auxiliary agent contains a carboxylic acid anhydride having a boiling point of 200° C. or higher and an oxygen atom content of 40% by weight or higher.

[0132] The binder removal aid has a large amount of oxygen atoms in its molecule, consumes its own oxygen and burns even in a nitrogen atmosphere, and assists the thermal decomposition of the binder resin by mixing with the binder resin. Therefore, the binder removal process can be promoted without increasing the oxygen partial pressure to significantly reduce the sintering residue, and the oxidation of inorganic particles can be suppressed to produce electronic components with high reliability.

[0133] From the viewpoint of debonding and suppressing oxidation of inorganic particles, the content of oxygen atoms in the above-mentioned carboxylic anhydride is 40% by weight or more, preferably 45% by weight or more, and more preferably 48% by weight or more. In addition, from the viewpoint of solubility in a solvent, the content of oxygen atoms is preferably 55% by weight or less, preferably 50% by weight or less. The content of oxygen atoms is preferably 40 to 55% by weight, more preferably 45 to 50% by weight, and further preferably 48 to 50% by weight.

[0134] The oxygen atom content is the content of oxygen atoms in one molecule, which can be calculated based on the molecular weight of the debindering aid and the atomic weight of oxygen. Alternatively, the oxygen atom content can be calculated by setting the atomic weight of carbon to 12, the atomic weight of hydrogen to 1, and the atomic weight of oxygen to 16.

[0135] The boiling point of the carboxylic anhydride is 200° C. or higher.

[0136] By setting it as the said boiling point, when the slurry composition is applied and dried, it does not evaporate together with a solvent, and can show the effect of accelerating a binder removal process.

[0137] The boiling point is preferably 390°C or lower, more preferably 250°C or higher, more preferably 370°C or lower, further preferably 270°C or higher, further preferably 350°C or lower. The boiling point is preferably 200-390°C, more preferably 250-370°C, further preferably 270-350°C.

[0138] The carboxylic acid anhydride having a boiling point of 270° C. or higher functions as a plasticizer. By using such a carboxylic acid anhydride as a debindering auxiliary agent, the amount of the plasticizer added can be reduced.

[0139] It should be noted that the above carboxylic anhydride starts to burn at less than 200°C in an air atmosphere, so the boiling point is preferably measured under reduced pressure. As a method for converting the boiling point under reduced pressure, the method of Science of Petroleum, Vol. II. p. 1281 (1938) can be used.

[0140] Examples of the carboxylic acid anhydride include anhydrides of succinic acid, maleic acid, citric acid, glutaric acid, diglycolic acid, methoxyacetic acid, itaconic acid, citraconic acid, trimellitic acid, cyclobutanetetracarboxylic acid, propanetricarboxylic acid, butanetetracarboxylic acid, cyclopentanetetracarboxylic acid, and malonic acid.

[0141] Among them, anhydrides of succinic acid, maleic acid, citric acid, glutaric acid, diglycolic acid, methoxyacetic acid, itaconic acid, citraconic acid, trimellitic acid, cyclobutanetetracarboxylic acid, propanetricarboxylic acid, butanetetracarboxylic acid, and cyclopentanetetracarboxylic acid are preferred, and anhydrides of succinic acid, maleic acid, citric acid, diglycolic acid, and methoxyacetic acid are more preferred.

[0142] The above-mentioned carboxylic anhydrides may be used alone or in combination of two or more.

[0143] By using the carboxylic anhydride as the binder removal aid, the binder removal process can be promoted without increasing the oxygen partial pressure, and the sintering residue can be significantly reduced. In addition, the oxidation of the inorganic particles can be suppressed, and a highly reliable electronic component can be produced.

[0144] Specific examples of the carboxylic anhydride include succinic anhydride (boiling point 261° C., oxygen content 48.0 wt %), maleic anhydride (boiling point 202° C., oxygen content 49.0 wt %), citric anhydride (boiling point 520° C., oxygen content 55.2 wt %), glutaric anhydride (boiling point 283° C., oxygen content 42.1 wt %), diglycolic anhydride (boiling point 240° C., oxygen content 55.2 wt %), itaconic anhydride (boiling point 232° C., oxygen content 42.9 wt %), citraconic anhydride (boiling point 213° C., oxygen content 42.9 wt %), trimellitic anhydride (boiling point 3 93℃, oxygen content 41.7 wt %), 1,2,3,4-cyclobutanetetracarboxylic dianhydride (boiling point 545℃, oxygen content 49.0 wt %), 2-methoxyacetic anhydride (boiling point 215℃, oxygen content 49.4 wt %), propanetricarboxylic anhydride (boiling point 390℃, oxygen content 50.6 wt %), 1,2,3,4-butanetetracarboxylic dianhydride (boiling point 492℃, oxygen content 48.5 wt %), 1,2,3,4-cyclopentanetetracarboxylic dianhydride (boiling point 527℃, oxygen content 45.7 wt %), malonic anhydride (oxygen content 55.8 wt %), etc.

[0145] Among them, succinic anhydride, maleic anhydride, citric anhydride, diglycolic anhydride, itaconic anhydride, citraconic anhydride, trimellitic anhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 2-methoxyacetic anhydride, propanetricarboxylic anhydride, 1,2,3,4-butanetetracarboxylic dianhydride, and 1,2,3,4-cyclopentanetetracarboxylic dianhydride are preferred because of their advantages of high oxygen content and high boiling point. Succinic anhydride, maleic anhydride, citric anhydride, diglycolic anhydride, and 2-methoxyacetic anhydride are more preferred.

[0146] The content of the above-mentioned carboxylic anhydride in the above-mentioned slurry composition is preferably 0.1% by weight or more, preferably 15% by weight or less, more preferably 0.2% by weight or more, more preferably 10% by weight or less, further preferably 0.4% by weight or more, and further preferably 5% by weight or less. By setting the above range, the debonding effect is fully improved, and the debonding aid will not precipitate in the slurry composition, which can make the printability excellent. The content of the above-mentioned carboxylic anhydride is preferably 0.1 to 15% by weight, more preferably 0.2 to 10% by weight, and further preferably 0.4 to 5% by weight.

[0147] The content of the carboxylic anhydride in the slurry composition is preferably 5 parts by weight or more, and preferably 30 parts by weight or less, based on 100 parts by weight of the binder resin (A).

[0148] By setting it as the said range, the binder removal effect can be fully improved, and the binder removal auxiliary agent will not precipitate in a slurry composition, and it can make excellent printing property.

[0149] The content of the carboxylic acid anhydride is preferably 8 parts by weight or more, preferably 25 parts by weight or less, more preferably 10 parts by weight or more, and more preferably 20 parts by weight or less. The content of the carboxylic acid anhydride is preferably 5 to 30 parts by weight, more preferably 8 to 25 parts by weight, and further preferably 10 to 20 parts by weight relative to 100 parts by weight of the binder resin (A).

[0150] Furthermore, the binder removal aid (D) may contain other binder removal aids such as inorganic oxides such as boric acid glass in addition to the carboxylic anhydride.

[0151] The content of the debindering aid (D) in the slurry composition is preferably 0.1% by weight or more, preferably 15% by weight or less, more preferably 0.2% by weight or more, more preferably 10% by weight or less, further preferably 0.4% by weight or more, further preferably 5% by weight or less. The content of the debindering aid (D) is preferably 0.1 to 15% by weight, more preferably 0.2 to 10% by weight, further preferably 0.4 to 5% by weight. By setting it in the above range, the debindering effect is fully improved, and the debindering aid will not precipitate in the slurry composition, which can make the printability excellent.

[0152] The content of the binder removal aid (D) in the slurry composition is preferably 5 parts by weight or more, and preferably 30 parts by weight or less, based on 100 parts by weight of the binder resin (A).

[0153] By setting it as the said range, the binder removal effect can be fully improved, and the binder removal auxiliary agent will not precipitate in a slurry composition, and it can make excellent printing property.

[0154] The content of the carboxylic acid anhydride is preferably 8 parts by weight or more, preferably 25 parts by weight or less, more preferably 10 parts by weight or more, and more preferably 20 parts by weight or less, relative to 100 parts by weight of the (meth)acrylic resin. The content of the carboxylic acid anhydride is preferably 5 to 30 parts by weight, more preferably 8 to 25 parts by weight, and further preferably 10 to 20 parts by weight, relative to 100 parts by weight of the (meth)acrylic resin.

[0155] (Other additives)

[0156] The slurry composition may contain other additives such as a plasticizer, a surfactant, and a dispersant in addition to the binder resin (A), the inorganic particles (B), the solvent (C), and the binder removal aid (D) containing a carboxylic anhydride.

[0157] Examples of the plasticizer include di(butoxyethyl) adipate, dibutoxyethoxyethyl adipate, triethylene glycol dibutyl ether, triethylene glycol bis(2-ethylhexanoate), triethylene glycol dicaproate, acetyl tributyl citrate, diethyl acetyl citrate, dibutyl acetyl citrate, dibutyl sebacate, triacetin, diethyl acetoxymalonate, and diethyl ethoxymalonate.

[0158] By using these plasticizers, the amount of plasticizer added can be reduced compared to the case of using a normal plasticizer.

[0159] It should be noted that the above-mentioned plasticizer is different from the above-mentioned debindering auxiliary agent.

[0160] In addition, since plasticizers having an aromatic ring such as a benzene ring in the structure are easily burned to form coal, it is preferable to use a non-aromatic plasticizer, and it is more preferable to contain a component derived from adipic acid, triethylene glycol, or citric acid.

[0161] The plasticizer is preferably a plasticizer having an alkyl group having 2 or more carbon atoms, such as an ethyl group or a butyl group, and more preferably a plasticizer having an alkyl group having 4 or more carbon atoms.

[0162] By containing an alkyl group having 2 or more carbon atoms, absorption of water into the plasticizer can be suppressed, and the resulting inorganic particle dispersed sheet can be prevented from having problems such as voids and swelling. It is particularly preferred that the alkyl group of the plasticizer is located at a molecular terminal.

[0163] Plasticizers having a substituent having 2 carbon atoms such as an ethyl group at the molecular end have good compatibility with segments derived from ethyl methacrylate, and plasticizers having a substituent having 4 carbon atoms such as a butyl group at the molecular end have good compatibility with segments derived from butyl methacrylate. Such plasticizers have good compatibility with the above-mentioned (meth) acrylic resins and can improve the brittleness of the resin. In addition, plasticizers having butoxyethyl groups have good compatibility with both segments derived from ethyl methacrylate and segments derived from butyl methacrylate, and can be preferably used.

[0164] The carbon:oxygen ratio of the plasticizer is preferably 5:1 to 3:1.

[0165] By setting the carbon:oxygen ratio to the above range, the combustibility of the plasticizer can be improved, and the generation of residual carbon can be prevented. In addition, the compatibility with the (meth)acrylic resin can be improved, and even a small amount of the plasticizer can exert a plasticizing effect.

[0166] Furthermore, high boiling point organic solvents having a propylene glycol skeleton or a trimethylene glycol skeleton can be preferably used if they contain an alkyl group having 4 or more carbon atoms and a carbon:oxygen ratio of 5:1 to 3:1.

[0167] The boiling point of the plasticizer is preferably 240°C or higher, and preferably lower than 390°C.

[0168] When it is within the above range, it is easy to evaporate in the drying step, and can be prevented from remaining in the molded body. Furthermore, it is also possible to prevent the generation of residual carbon.

[0169] It should be noted that the above-mentioned boiling point refers to the boiling point under normal pressure.

[0170] The content of the plasticizer in the slurry composition is not particularly limited, but is preferably 0.1% by weight or more and preferably 3.0% by weight or less. The content of the plasticizer is preferably 0.1 to 3.0% by weight.

[0171] By setting it as the said range, sheet handling property and sintering property can be achieved at the same time.

[0172] Examples of the surfactant include cationic surfactants, anionic surfactants, and nonionic surfactants.

[0173] As the above-mentioned nonionic surfactant, there is no particular limitation, and a nonionic surfactant having an HLB value of 10 or more and 20 or less is preferred. Here, the HLB value is used as an index to indicate the hydrophilicity and lipophilicity of the surfactant, and several calculation methods are proposed. For example, for ester-based surfactants, there are definitions such as setting the saponification value to S, setting the acid value of the fatty acid constituting the surfactant to A, and setting the HLB value to 20 (1-S / A). Specifically, a nonionic surfactant having a polyethylene oxide with an alkylene ether added to the fatty chain is suitable, and specifically, for example, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, etc. are suitable. It should be noted that the above-mentioned nonionic surfactant has good thermal decomposition, but if it is added in large quantities, the thermal decomposition of the inorganic particle dispersion slurry composition is sometimes reduced, so the preferred upper limit of the content is 5% by weight.

[0174] As the above-mentioned dispersant, for example, fatty acids, aliphatic amines, alkanolamides, and phosphoric acid esters are suitable. In addition, a silane coupling agent or the like may be added.

[0175] The fatty acid is not particularly limited, and examples thereof include saturated fatty acids such as behenic acid, stearic acid, palmitic acid, myristic acid, lauric acid, capric acid, caprylic acid, and coconut oil fatty acids; unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, sorbic acid, tallow fatty acid, and hydrogenated castor oil fatty acids (Japanese: himasi hardened fatty acids), etc. Among them, lauric acid, stearic acid, oleic acid, etc. are suitable.

[0176] The aliphatic amine is not particularly limited, and examples thereof include laurylamine, myristicamine, cetylamine, stearylamine, oleylamine, alkyl(coconut)amine, alkyl(hydrogenated tallow)amine, alkyl(tallow)amine, and alkyl(soybean)amine.

[0177] The alkanolamide is not particularly limited, and examples thereof include coconut oil fatty acid diethanolamide, tallow fatty acid diethanolamide, lauric acid diethanolamide, and oleic acid diethanolamide.

[0178] The phosphoric acid ester is not particularly limited, and examples thereof include polyoxyethylene alkyl ether phosphoric acid ester and polyoxyethylene alkyl allyl ether phosphoric acid ester.

[0179] Since the slurry composition contains the carboxylic anhydride as the binder removal aid (D), it is preferred that the water content is low. The water content is preferably 1% by weight or less, and more preferably 0.1% by weight or less.

[0180] The method for reducing the water content is not particularly limited, and examples thereof include a reduced pressure degassing method and a molecular sieve method.

[0181] The viscosity of the slurry composition is not particularly limited, but when measured at 20° C. using a B-type viscometer with a probe rotation speed set to 5 rpm, the preferred lower limit of the viscosity is 0.1 Pa·s, and the preferred upper limit is 100 Pa·s. The viscosity is preferably 0.1 to 100 Pa·s.

[0182] By setting the viscosity to 0.1 Pa·s or more, the obtained inorganic particle dispersion sheet can maintain a predetermined shape after being coated by die coating printing method, etc. In addition, by setting the viscosity to 100 Pa·s or less, it is possible to prevent the coating trace of the die head from disappearing, thereby achieving excellent printability.

[0183] The method for preparing the slurry composition is not particularly limited, and a conventionally known stirring method may be mentioned. Specifically, for example, the binder resin (A), the inorganic particles (B), the solvent (C), the binder removal aid (D) containing the carboxylic anhydride, and other additives added as needed are mixed and stirred using a three-roll mill or the like.

[0184] By using the above-mentioned slurry composition, electronic components, magnets such as neodymium magnets, and the like can be produced.

[0185] Examples of the electronic components include die attach paste (ACP), die attach film (ACF), via electrodes for TSV and TGV, touch panels, RFID, various circuits of sensor substrates, various die bonding agents, sealants for MEMS devices, solar cells, laminated ceramic capacitors, LTCC, silicon capacitors, electrode materials for all-solid-state batteries, etc. In addition to the electrode circuit applications, the materials can also be used for piezoelectric elements, inductors, sintered magnets, antibacterial components, electromagnetic wave shielding, catalysts, fluorescent materials, etc.

[0186] For example, the slurry composition is applied onto a substrate and dried to produce an inorganic particle dispersion compact. The obtained inorganic particle dispersion compact is further subjected to heat treatment to remove the binder (degreasing), and then heated to the sintering temperature of the inorganic particles to be fired, thereby obtaining an inorganic sintered body.

[0187] A method for producing an inorganic sintered body comprising the steps of drying the inorganic particle-dispersed slurry composition to obtain an inorganic particle-dispersed compact and degreasing the inorganic particle-dispersed compact at 300° C. or lower is also one of the present invention.

[0188] The forming method of the inorganic particle dispersion slurry composition is not particularly limited, and the composition can be formed into a coil shape by alternately applying a screen plate with a U-shaped opening up and down, or directly printing on a substrate to form a laminate, or the inorganic particle dispersion slurry composition can be dip-coated on a substrate. The forming can be performed by screen printing or the like by using a high boiling point solvent.

[0189] The inorganic particle-dispersed sheet can be produced by applying the slurry composition onto a support film subjected to a release treatment on one side and drying the solvent to obtain a sheet-shaped inorganic particle-dispersed compact.

[0190] The thickness of the inorganic particle dispersed sheet is preferably 1 to 20 μm.

[0191] As the coating method, for example, a coating method using a roll coater, a die coater, an extrusion coater, a curtain coater or the like can be used.

[0192] Examples of the drying method include heat drying and the like.

[0193] The drying temperature is preferably 80° C. or higher and preferably 130° C. or lower.

[0194] The support film used when manufacturing the above-mentioned inorganic particle dispersion sheet is preferably a resin film with heat resistance and solvent resistance and flexibility. By making the support film flexible, the inorganic particle dispersion slurry composition can be applied to the surface of the support film using a roll coater, a scraper coater, etc., and the obtained inorganic particle dispersion sheet can be formed into a film and stored and supplied in a state of being wound into a roll.

[0195] Examples of the resin forming the support film include polyethylene terephthalate, polyester, polyethylene, polypropylene, polystyrene, polyimide, polyvinyl alcohol, fluorine-containing resins such as polyvinyl chloride and polyvinyl fluoride, nylon, and cellulose.

[0196] The thickness of the support film is preferably, for example, 20 to 100 μm.

[0197] In addition, it is preferable to subject the surface of the support film to a release treatment, whereby the support film can be easily peeled off in the transfer step.

[0198] The inorganic sintered body can be obtained by performing a debinding step of heat-treating the inorganic particle-dispersed compact to remove the binder (debinding), and then performing a sintering step of heating to a sintering temperature of the inorganic particles to sinter the compact.

[0199] The degreasing step is preferably performed at 300° C. or lower.

[0200] By using the above slurry composition, the binder removal treatment can be sufficiently performed even in a low temperature environment of 300° C. or lower.

[0201] The temperature is preferably 250°C or higher and preferably 280°C or lower.

[0202] The time for maintaining the above temperature is preferably 0.1 hour or longer and preferably 1 hour or shorter.

[0203] Furthermore, the temperature increase rate is preferably 20° C. / min or more and preferably 100° C. / min or less.

[0204] In the case where the inorganic particles used are easily deteriorated by oxygen in the air, the above degreasing process is preferably carried out in a nitrogen atmosphere. In addition, in the case where the inorganic particles used are relatively stable to oxygen in the air, the above degreasing process can also be carried out in an air atmosphere. In the case of carrying out the degreasing process in an air atmosphere, the binder removal process can be carried out more quickly than in a nitrogen atmosphere, and the sintering residue remaining in the sintered body can be reduced.

[0205] After the degreasing step, a sintering step of heating to a sintering temperature of the inorganic particles is performed.

[0206] Thereby, an inorganic sintered body can be obtained.

[0207] The calcination temperature is appropriately set depending on the type of inorganic particles and is not particularly limited, but is, for example, 300° C. or higher and 1000° C. or lower.

[0208] In addition, the temperature increase rate is preferably 20° C. / minute or more and preferably 100° C. / minute or less.

[0209] The calcination step may be performed in a nitrogen atmosphere, an air atmosphere, a vacuum atmosphere, or a reducing atmosphere containing a trace amount of hydrogen.

[0210] By using ceramic powder as the inorganic particles (B) in the slurry composition, a ceramic sintered body can be produced.

[0211] The ceramic sintered body may be a ceramic laminate or a ceramic single layer body.

[0212] The above-mentioned ceramic laminates can be used for laminated ceramic capacitors, laminated ceramic substrates, all-solid-state batteries, etc., and the ceramic single-layer bodies can be used for ceramic packaging, low-temperature co-fired ceramics (LTCC), circuit substrates such as alumina, ceramic heat dissipation substrates such as aluminum nitride and silicon nitride, electrostatic chucks, ceramic columns, temperature sensors, piezoelectric elements, various mechanical parts, etc.

[0213] By using the slurry composition and the inorganic particle dispersion sheet as materials for the positive electrode, solid electrolyte, and negative electrode of an all-solid-state battery, an all-solid-state battery can be manufactured. In addition, by using the slurry composition and the inorganic particle dispersion sheet as dielectric green sheets and electrode pastes, a laminated ceramic capacitor can be manufactured.

[0214] The manufacturing method of the above-mentioned all-solid-state battery preferably has the following steps: a step of using the above-mentioned slurry composition to prepare an inorganic particle dispersion sheet; a step of forming an electrode active material layer slurry containing an electrode active material and a binder for an electrode active material layer to prepare an electrode active material sheet; a step of stacking the above-mentioned electrode active material sheet and the above-mentioned inorganic particle dispersion sheet to prepare a stacked body; and a step of sintering the above-mentioned stacked body.

[0215] The method for producing a laminated ceramic capacitor preferably comprises the steps of: preparing an inorganic particle dispersion sheet using the slurry composition; printing a conductive paste on the inorganic particle dispersion sheet and drying the printed conductive paste to prepare a dielectric sheet; and laminating the dielectric sheets.

[0216] The above-mentioned conductive paste contains conductive powder.

[0217] The material of the conductive powder is not particularly limited as long as it has conductivity, and examples thereof include nickel, palladium, indium, platinum, gold, silver, copper, and alloys thereof. These conductive powders may be used alone or in combination of two or more.

[0218] The method for printing the conductive paste is not particularly limited, and examples thereof include screen printing, die coating printing, offset printing, gravure printing, and inkjet printing.

[0219] In the method for manufacturing the multilayer ceramic capacitor, the multilayer ceramic capacitor can be obtained by laminating the dielectric sheet on which the conductive paste is printed and the electrode layer.

[0220] An electronic component can be manufactured by sintering a raw ceramic component on which the inorganic particle dispersion sheet containing the binder removal aid and the conductive paste composition are stacked to produce a sintered ceramic component, and further providing external electrodes.

[0221] The conditions for firing are not particularly limited, but firing is preferably performed in an inert gas or reducing gas atmosphere so that the transition metal used in the electrode layer is not oxidized.

[0222] In addition, the binder removal step and the inorganic particle calcining step can be maintained at a temperature suitable for the purpose.

[0223] The binder removal step is carried out by maintaining the temperature at 250°C to 350°C for 1 to 3 hours in an inert gas atmosphere, thereby reducing the content of organic matter such as binders and plasticizers to less than 20%, and then transferring to the inorganic particle sintering step. The inorganic particle sintering step is carried out by heating the inorganic particles from 800°C to 1300°C in an inert gas atmosphere or a reducing gas atmosphere. The heating rate is preferably 5°C / min to 100°C / min.

[0224] By providing external electrodes on the fired ceramic component, an electronic component can be manufactured.

[0225] The composition and setting method of the external electrode are not particularly limited. Metal plating, thermosetting conductive resin, metal paste, etc. can be preferably used. The metal that can be used for the metal paste is preferably a metal that has high conductivity and sintered at a low temperature. For example, copper, nickel, silver, palladium, etc. can be mentioned.

[0226] For example, Nd is used in the above slurry composition. 2 Fe 14 When B is inorganic particles (B), the slurry composition is applied to a ferrite magnet substrate, dried, pressed with magnetic force, and fired at about 300° C. while magnetically orienting the slurry, thereby producing a neodymium magnet with suppressed reduction in magnetic force.

[0227] In addition, for example, when using La 2 / 3-x Li 3x TiO 3 In the case where (LLTO) is used as the inorganic particle (B), the above-mentioned slurry composition is applied to the negative electrode Li foil and dried, and then laminated to a positive electrode sheet containing LLTO as a positive electrode, acetylene black as a conductive aid, lithium niobate as a positive electrode active material, etc., and sintered at about 300°C, thereby manufacturing a large-capacity all-solid-state battery.

[0228] Furthermore, a multilayer ceramic capacitor can be manufactured by using a configuration in which a slurry composition using barium titanate as the inorganic particles (B) and a slurry composition using nickel particles as the inorganic particles (B) are combined.

[0229] In addition, an inductor can be manufactured by using a structure in which a slurry composition using Ni—Zn—Cu ferrite as the inorganic particles (B) and a slurry composition using copper particles as the inorganic particles (B) are combined.

[0230] When the sinterability of the inorganic particles (B) is insufficient during sintering at about 300° C., borosilicate, phosphate, or the like may be added as a sintering aid.

[0231] Effects of the Invention

[0232] According to the present invention, an inorganic particle-dispersed slurry composition can be provided, which has excellent storage stability and printability, can promote debindering even at low temperatures, can inhibit the oxidation of inorganic particles, has little residual carbon after firing and excellent sintering properties, and can obtain electronic components with high reliability. In addition, a method for producing an inorganic sintered body using the slurry composition can be provided. DETAILED DESCRIPTION

[0233] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0234] <Production of (meth)acrylic resin>

[0235] (Synthesis example 1)

[0236] A 2L separable flask equipped with a stirrer, a cooler, a thermometer, a hot water bath, and a nitrogen inlet was prepared. 50 parts by weight of isobutyl methacrylate (iBMA) was added to the 2L separable flask. Furthermore, 50 parts by weight of n-butyl methacrylate (nBMA) was added. Furthermore, 100 parts by weight of terpineol as an organic solvent was mixed to obtain a monomer mixed solution.

[0237] After nitrogen was bubbled into the monomer mixture to remove dissolved oxygen, the temperature in the flask was raised to 80° C. using a hot water bath. Then, 2.0 parts by weight of lauroyl peroxide as a polymerization initiator was added in several portions, and polymerization was completed after 6 hours to obtain a composition containing a (meth)acrylic resin. The resin solid content was 50.0% by weight.

[0238] The obtained (meth)acrylic resin-containing composition was dried and dissolved in tetrahydrofuran (THF) at a resin concentration of 0.1 wt %. The polystyrene-equivalent weight average molecular weight (Mw) was measured by GPC using SHODEX LF-804 as a column. The results of Mw are shown in Table 1.

[0239] (Synthesis example 2)

[0240] A 2L separable flask equipped with a stirrer, a cooler, a thermometer, a hot water bath, and a nitrogen inlet was prepared. 60 parts by weight of isobutyl methacrylate (iBMA) and 20 parts by weight of 2-ethylhexyl methacrylate (2EHMA) were added to the 2L separable flask. Furthermore, 20 parts by weight of n-butyl methacrylate (BMA) was added. Furthermore, 10 parts by weight of butyl acetate as an organic solvent was mixed to obtain a monomer mixed solution.

[0241] After nitrogen was bubbled into the monomer mixture to remove dissolved oxygen, the temperature in the flask was raised to 80° C. using a hot water bath. 2.0 parts by weight of lauroyl peroxide was added as a polymerization initiator in several portions, and polymerization was completed after 6 hours. The resin solid content was 90.9% by weight.

[0242] (Synthesis example 3)

[0243] A (meth)acrylic resin was prepared in the same manner as in Synthesis Example 1 except that the amount of iBMA added was 40 parts by weight and the amount of nBMA added was 60 parts by weight.

[0244] (Synthesis example 4)

[0245] A (meth)acrylic resin was prepared in the same manner as in Synthesis Example 2 except that the amount of iBMA added was 40 parts by weight, 2EHMA was not added, and the amount of nBMA added was 60 parts by weight.

[0246] (Example 1)

[0247] 10.0 parts by weight of the (meth)acrylic resin obtained in Synthesis Example 1 as a binder resin (A) and 2.0 parts by weight of succinic anhydride as a binder removal aid (D) were added to 38.0 parts by weight of pine alcohol as a solvent (C) and uniformly dissolved using a high-speed stirrer. Furthermore, lithium sulfide glass powder Li 20 was added as an inorganic particle (B). 10 G 2 S 12 50.0 parts by weight of LGPS (LGPS, average particle size 10 μm) was used to disperse inorganic particles using a triple roll mill to obtain an inorganic particle-dispersed slurry composition.

[0248] The obtained slurry composition was used to print a 5 cm square print image on a ceramic plate using a screen printer, and dried in an air-supplemented oven set at 120° C. for 30 minutes to obtain a printed substrate.

[0249] The obtained printed circuit board was heat-treated for 60 minutes in an electric furnace set at an internal temperature of 280° C. and the interior thereof replaced with nitrogen gas to complete degreasing, thereby obtaining a fired circuit board.

[0250] (Example 2)

[0251] Li as inorganic particles (B) 2 SP 2 S 550.0 parts by weight of glass powder (average particle size 10 μm) and 38.0 parts by weight of butyl acetate as a solvent (C) were mixed, and the inorganic particles (B) were stirred for 2 hours using a closed bead mill. Then, 10.0 parts by weight of the (meth)acrylic resin obtained in Synthesis Example 2 as a binder resin (A) and 2.0 parts by weight of maleic anhydride as a debindering aid (D) were added, and the mixture was further stirred for 3 hours to obtain an inorganic particle dispersed slurry composition.

[0252] The obtained slurry composition was printed on an indium substrate using a die coater, and dried in an air-supplemented oven set at 120° C. for 30 minutes to obtain a printed substrate.

[0253] The obtained printed circuit board was heat-treated for 60 minutes in an electric furnace set at an internal temperature of 280° C. and the interior thereof replaced with nitrogen gas to complete degreasing, thereby obtaining a fired circuit board.

[0254] (Examples 3 to 5, Comparative Examples 1, 3, 4, 6)

[0255] Except having used the formulation described in Table 1, the same operation as in Example 1 was carried out to obtain an inorganic particle-dispersed slurry composition and a fired substrate.

[0256] It should be noted that when using Nd 2 Fe 14 B (average particle size 5 μm) In Examples 3 to 5 and Comparative Example 3, which used inorganic particles (B), the inner temperature of the electric furnace was set to 300° C. for degreasing, and then sintered at 700° C. for 1 hour in a nitrogen atmosphere to obtain sintered substrates.

[0257] (Examples 6 to 8, Comparative Examples 2, 5, and 7)

[0258] Except having used the formulation described in Table 1, it carried out similarly to Example 2, and obtained the inorganic particle dispersion slurry composition and the fired substrate.

[0259] It should be noted that when using Sm 2 Fe 17 N 3 (Average particle size 5 μm) In Examples 6 and 7 and Comparative Example 5 as the inorganic particles (B), after degreasing by setting the internal temperature of the electric furnace to 300° C., the substrates were fired at 400° C. for 1 hour in a nitrogen atmosphere to obtain fired substrates.

[0260] In Example 8 and Comparative Example 7 using GaN (average particle size 3 μm) as the inorganic particles (B), after degreasing by setting the internal temperature of the electric furnace to 300° C., the substrates were fired at 1100° C. for 2 hours in a nitrogen atmosphere to obtain fired substrates.

[0261] (Comparative Example 8)

[0262] Except having used the formulation described in Table 3, it carried out similarly to Example 1, and obtained the inorganic fine particle dispersion slurry composition.

[0263] The obtained slurry composition was printed on an indium substrate using a die coater, and dried in an air-supplemented oven set at 120° C. for 30 minutes to obtain a printed substrate.

[0264] The obtained printed circuit board was heat-treated for 60 minutes in an electric furnace in a dry air atmosphere at an internal temperature of 300° C. to complete degreasing and obtain a fired circuit board.

[0265] (Example 9, Comparative Example 9)

[0266] Except having used the formulation described in Table 3, the same operation as in Example 2 was carried out to obtain an inorganic particle-dispersed slurry composition and a fired substrate.

[0267] (Example 10, Comparative Example 10)

[0268] Except having used the formulation described in Table 3, the same operation as in Example 3 was carried out to obtain an inorganic particle-dispersed slurry composition and a fired substrate.

[0269] (Comparative Example 11)

[0270] Except having used the formulation described in Table 3, it carried out similarly to Example 6, and obtained the inorganic particle dispersion slurry composition and the fired substrate.

[0271] (evaluate)

[0272] The obtained slurry composition and fired substrate were evaluated as follows. The results are shown in Tables 2 and 4.

[0273] (1) Viscosity

[0274] For the obtained slurry composition, the viscosity at 25°C was measured using a B-type viscometer immediately after preparation. In addition, after standing for 2 weeks after preparation, the viscosity at 25°C was similarly measured. Furthermore, the viscosity change rate was calculated by the following formula using the viscosity immediately after preparation and after 2 weeks, and the evaluation was performed according to the following criteria. It should be noted that if the viscosity change rate is small, it can be said that the storage stability is excellent.

[0275] Viscosity change rate (%) = | (viscosity after 2 weeks - viscosity immediately after production) / (viscosity immediately after production) | × 100

[0276] 0: Viscosity change rate is less than 20%.

[0277] ×: The viscosity change rate is 20% or more.

[0278] (2)Printability

[0279] Visually confirm the printed image on the printed circuit board and evaluate it according to the following criteria.

[0280] 〇: There is no white streaking (Japanese: 掠れ), bleeding (Japanese: 滲み), etc., and it is good.

[0281] ×: Defects such as white streaking and bleeding are confirmed.

[0282] (3)Residual carbon

[0283] Crush the obtained fired substrate, and measure the residual carbon content based on the amount of CO and CO 2 measured by the combustion-infrared absorption method using a high-frequency induction heating furnace, and evaluate it according to the following criteria.

[0284] 〇: The residual carbon content is 200 ppm or less.

[0285] ×: The residual carbon content exceeds 200 ppm.

[0286] (4)Oxygen content

[0287] For the obtained fired substrate, use an oxygen-nitrogen analyzer EMGA-920 to measure the oxygen content and evaluate it according to the following criteria.

[0288] 〇: The oxygen content is less than 0.2 wt%.

[0289] ×: The oxygen content is 0.2 wt% or more.

[0290] (5)Cross-section observation

[0291] Use SEM to observe the cross-section of the obtained fired substrate and evaluate it according to the following criteria. It should be noted that the voids in the sintered substrate are considered to be caused by the decomposition of the resin. In the case of fewer voids, it can be said that more reliable electronic components can be obtained.

[0292] 〇: No voids are confirmed.

[0293] △: One or more but less than 10 voids are confirmed.

[0294] ×: Ten or more voids are confirmed.

[0295] [Table 1]

[0296]

[0297] [Table 2]

[0298]

[0299]

[0300] [Table 4]

[0301]

[0302] Industrial Applicability

[0303] According to the present invention, an inorganic particle-dispersed slurry composition can be provided, which has excellent storage stability and printability, can promote debindering even at low temperatures, can inhibit the oxidation of inorganic particles, has little residual carbon after firing and excellent sintering properties, and can obtain electronic components with high reliability. In addition, a method for producing an inorganic sintered body using the slurry composition can be provided.

Claims

1. An inorganic particle dispersion slurry composition comprising a binder resin A, inorganic particles B and a solvent C, The inorganic particle dispersion slurry composition further contains, as a debindering aid D, a carboxylic anhydride having a boiling point of 200° C. or higher and an oxygen atom content of 40% by weight or higher.

2. The inorganic particle dispersion slurry composition according to claim 1, wherein The carboxylic acid anhydride is an anhydride of at least one carboxylic acid selected from succinic acid, maleic acid, citric acid, glutaric acid, diglycolic acid, methoxyacetic acid, itaconic acid, citraconic acid, trimellitic acid, cyclobutanetetracarboxylic acid, propanetricarboxylic acid, butanetetracarboxylic acid, and cyclopentanetetracarboxylic acid.

3. The inorganic particle-dispersed slurry composition according to claim 1 or 2, wherein: The content of the carboxylic anhydride is 5 parts by weight or more and 30 parts by weight or less relative to 100 parts by weight of the binder resin A.

4. The inorganic particle-dispersed slurry composition according to any one of claims 1 to 3, wherein The binder resin A includes a (meth)acrylic resin.

5. The inorganic particle-dispersed slurry composition according to claim 4, wherein The (meth)acrylic resin contains 50% by weight or more of a segment derived from a (meth)acrylic acid ester having 4 or more carbon atoms in an ester substituent and having a branched structure in the ester substituent.

6. A method for producing an inorganic sintered body, comprising: A step of drying the inorganic particle-dispersed slurry composition according to any one of claims 1 to 5 to obtain an inorganic particle-dispersed compact; and a step of degreasing the inorganic particle dispersed compact at a temperature below 300° C.

Citation Information

Patent Citations

  • Glass paste

    JP2011178606A

  • Laminate green sheet and all-solid type secondary battery

    JP2018077989A

Cited By

  • Composite yttrium oxide ceramic and preparation method thereof

    CN120441278A

  • A composite yttrium oxide ceramic and its preparation method

    CN120441278B